Influence of different playing styles among the top three teams on action zones in the World Cup in 2018 using a Markov state transition matrix - Liu, Tianbiao; Zhou, Chenye; Shuai, Xumei; Zhang, Li; Zhou, Jingjing; Yang, Lang (Frontiers in Psychology, 2022)
Purpose: In football, attacking has seen evolving for decades and attacking pattern detection is important topic in this sport. The purpose of this study was to identify the general and threatening attacking patterns of different playing styles in world top football matches, which represented the latest evolvement of soccer attacking. Methods: Attacking sequence data of the top three teams from 21 matches in the 2018 World Cup were collected. The three teams were classified into two playing styles according to previous study, France was a direct play team, and Croatia and Belgium were possession play teams. The football field was divided into 12 zones and Markov transition matrix-based zone models were applied to assess the attacking pattern in the 21 matches. Both descriptive analysis and simulative analysis were conducted using this model. Results: The results revealed that 1) flanker attacks were frequently taken among all three teams, and possession playing teams (Croatia and Belgium) played more often than direct playing teams (France) in their centre of the midfield zone; and 2) forward passes across/through zones towards the middle of attacking quarter (A1/4) have a positive impact of creating a chance of a goal. Conclusion: Using Markov transition matrix, general and threatening attacking patterns were found. The combination of possession-play and counterattack was a new trend that emerged in the 2018 World Cup. These findings can help coaches to develop corresponding strategies when facing opponents of different playing styles.